Ultrastructural Analysis of Rehydrated Human Donor Corneas After Air-Drying and Dissection by Femtosecond Laser - Pedrotti, Emilio; Bonacci, Erika; Fasolo, Adriano; De Rossi, Arianna; Camposampiero, Davide; Jones, Gary L. A.; Bernardi, Paolo; Merigo, Flavia; Ponzin, Diego; Marchini, Giorgio; Sbarbati, Andrea (Frontiers in Medicine, 2021)
Purpose: To evaluate the efficiency of femtosecond laser incision of rehydrated human corneas after air-drying and its effects on corneal structure. Methods: We compared by microscopy rehydrated and fresh-preserved corneas following Victus-Tecnolas femtosecond laser treatment for straight-edge anterior lamellar keratoplasty. The corneas were dehydrated at room temperature under a laminar-flow hood. Results: To incise the rehydrated corneas, we increased the femtosecond laser pulse energy from 0.80 µJ to 1.2 µJ and obtained a clear-cut separation of the lamellar lenticule cap from the cornea bed. Light microscopy showed regular arrangement of stromal collagen lamellae, with spaces in between the fibers in the corneal stroma in the fresh and the rehydrated corneas, but the uppermost epithelial layers in the rehydrated corneas were lost. Transmission electron microscopy revealed no signs of thermal or mechanical damage to the corneal structure. The epithelial basal membrane and Bowman’s layer maintained their integrity. The epithelial basal layer and cells were separated by large spaces due to junction alteration in the rehydrated corneas. There were gaps between the lamellar layers in the stroma, especially in the rehydrated corneas. Keratocytes displayed normal structure in the fresh corneas but were devoid of microorganules in the rehydrated corneas. Minor irregularities were seen in the vertical incision and the horizontal stroma appeared smooth on scanning electron microscopy. Conclusion: The rehydrated corneas maintained their morphology and integrity. When corneas are intended for femtosecond laser-assisted anterior lamellar keratoplasty, effective stromal bed incision is best achieved at a laser power slightly higher than that currently adopted for fresh corneas.